Comparative study ofstomach contens of Rasbora cudimaculata from the Tanjung Kudu Lake and the Teluk Petai Lake, Kampar Regency, Riau Province - Saragih, Deliana; Efizon, Deni; Windarti, Windarti (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract             Rasbora caudimaculata is a type of freshwater fish that inhabits the Tanjung Kudu and the Teluk Petai Lakes, Kampar Regency. A study aims to understand the type of food in the stomach of the fish was conducted in October – January 2021. Samplings were carried out 4 times, once/2 weeks. The fish was caught using nets with mesh size 0.5 inch and 1 inch. There were 321 fishes (169 fishes from the Tanjung Kudu Lake and 152 fishes from the Teluk Petai Lake).  There were 58 fishes with empty stomach and they cannot be analyzed. The analysis of stomach content was conducted using a volumetric method. The stomach content data obtained were used as a basis to calculate the Preponderance Index (PI). The types of food present in the fish’s stomach from both sampling areas were similar. The main food of R. caudimaculata from both   lakes is insects, PI 55% from the Tanjung Kudu Lake and PI 46% from the Teluk Petai Lake. The complementary foods were phytoplankton (Bacillariophyceae, Chlorophyceae, Cyanophyceaea, Euglenoidea, Trebouxiophyceae, Xanthophyceae dan Zygnematophyceae) and rotifers. R. caudimaculata has viliform teeth and short firm gill rakers. The length of intestine was 1.2 times of total length. Data obtained indicate that R. caudimaculata is an omnivorous fish.Keywords: Oxbow lake, Feeding habit, Omnivorous fish, Preponderance Index